Model generation and comparative analysis of legal knowledge bases - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 2023)
The article deals with the possibilities of computerized comparative legal analysis. Legal documents are formalized using frame logic (F-logic) and are stored in knowledge bases. Their difference is defined as the difference between conclusions made from possible cases. This article presents an elaborated rule of knowledge base model generation designed for F-logic expressions.